Low Cerebrospinal Fluid Levels of Melanotransferrin Are Associated With Conversion of Mild Cognitively Impaired Subjects to Alzheimer’s Disease - Ashraf, Azhaar; Alepuz Guillen, Jose Andres; Aljuhani, Manal; Hubens, Chantal; So, Po-Wah (Frontiers in Neuroscience, 2019)
The disruption of iron metabolism and iron transport proteins have been implicated in the pathogenesis of Alzheimer’s disease (AD). Serum melanotransferrin (MTf), a transferrin homolog capable of reversibly binding iron, has been proposed as a biochemical marker of AD. MTf has also been shown to be elevated in iron-rich reactive microglia near amyloid plaques in AD. We examined the association of CSF MTf to hippocampal volumes and cognitive tests in 86 cognitively normal, 135 mild cognitive impairment (MCI) and 66 AD subjects. CSF was collected at baseline for MTf, Aβ, total-tau and phosphorylated-tau measurements. Serial cognitive testing with ADAS-Cog13, Rey’s auditory visual learning test (RAVLT), mini-mental state examination (MMSE) were performed alongside hippocampal MRI volumetric analysis for up to ten years after baseline measurements. High levels of baseline CSF MTf were positively associated with hippocampal volume (R2 = 22%, β = 0.202, p = 0.017) and RAVLT scores (R2 = 7.30%, β = -0.178, p = 0.043) and negatively correlated to ADAS-Cog13 (R2 = 17.3%, β = 0.247, p = 0.003) scores in MCI subjects. Interestingly, MCI subjects that converted to AD demonstrated significantly lower levels of CSF MTf (p = 0.020) compared to MCI non-converters at baseline. Diminished CSF MTf observed in MCI-converters to AD may arise from impaired transcytosis of MTf from blood into the brain tissue/CSF and/or increased MTf export from the CSF into the blood arising from attenuated competition with reduced levels of CSF Aβ. Further investigations are required to determine the source of CSF MTf and how brain MTf is regulated by cellular barriers, Aβ and activated microglia surround plaques in AD pathophysiology. In conclusion, low CSF MTf may identify those MCI individuals at risk of converting to AD.